Audit Quality: Providing a Model and Investigating The Gap Between the Current Situation and The Desired Level - AliAkbar Javan; jafar babajani; mohamad marfo; Farrokh Barzideh (مطالعات تجربی حسابداری مالی, 2023)
In this study by using the Fuzzy Delphi research methodology and getting the expert opinions, it was tried to identify indicators for improving audit quality approved by experts in order to design a suitable model for the Economy of IRAN by utilizing a confirmatory factor analysis model. Also in this research, the gap between current and desired situation of audit quality indicators in IRAN is investigated. Finally, the dimensions of audit quality are ranked in terms of importance. For this purpose, following the International Auditing and Assurance Standards Board, 60 indicators were identified. These indicators were classified in five dimensions: a. Input factors with 21 indicators; B. Process factors with 10 indicators; C. Output factors with 9 indicators; D. Key interactions with 10 indicators; and E. Contextual factors by 10 indicators. Data were analyzed by utilizing R, Amos and Super Decisions software. The findings indicate that 54 indicators have been adopted, which provide a model for improving the Audit Quality. Also the results of comparing the current and desired situation of audit quality improvement indicators shows a significant difference between the current situation of the audit quality and the desired environment in Iran. Finally, the results of ranking the dimensions affecting the improvement of audit quality Shows that process factors are in the first place of importance from the point of view of experts, input factors are in the second place, main interactions and contextual factors are both in the third place and output factors are in the fourth place.